2016
DOI: 10.4314/njp.v43i3.14
|View full text |Cite
|
Sign up to set email alerts
|

A Call for sting treatment protocol: Case report of a 3 year old with massive bee sting resulting in acute kidney injury

Abstract: Acute Kidney Injury in children following bee sting envenomation is rare and survival is hinged on early recognition and prompt appropriate management. This report is aimed at raising awareness among healthcare workers, of one of the systemic effects of massive bee sting and the need to develop sting treatment protocol. A three year old preschooler was attacked by a swarm of bees, receiving over 150stings. Initial clinical features were allergic response involving the head, face and tongue for which he had fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…26 Many studies in recent years have focused on the reasons, 27 prevalence, 6 pathological mechanism, 28 and treatment of honeybee venom stimulation. 3 Although some studies have yielded knowledge about the complex response of an organism to honeybee venom stimulation, the exact mechanism of response has still not been fully explained. Moreover, there is virtually no or very little literature about the effect of honeybee venom at the metabolic level, especially the changes at different time points.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Many studies in recent years have focused on the reasons, 27 prevalence, 6 pathological mechanism, 28 and treatment of honeybee venom stimulation. 3 Although some studies have yielded knowledge about the complex response of an organism to honeybee venom stimulation, the exact mechanism of response has still not been fully explained. Moreover, there is virtually no or very little literature about the effect of honeybee venom at the metabolic level, especially the changes at different time points.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to European and American population-based studies, the lifetime occurrence of a systemic reaction to honeybee venom ranges from 0.3 to 7.5% in adults and depends upon various factors, such as geography, study population, venom used for diagnosis, and the profession and hobbies of the subject . Studies have shown that honeybee venom administration could stimulate the function of the immune system and affect the release of cortisol production, which is known as a natural anti-inflammatory agent . The typical reaction of one organism to honeybee venom ranges from a smaller local reaction to a larger effect, with the most serious circumstance leading to anaphylaxis and death .…”
Section: Introductionmentioning
confidence: 99%
“…AKI in children after bee sting has been reported elsewhere [ 8 ]. Bee sting leaves stings behind which release venom amounting to 50–140 µg/sting which is a large dose enough to cause systemic damage [ 2 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both hemodialysis and peritoneal dialysis have been used to treat AKI following multiple bee sting effectively with good outcomes [ 2 , 4 , 5 , 8 , 9 , 11 ]. Although dialysis does not clear the bee venom, maintenance of good hydration and urine output are necessary in management of bee sting venom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation